앞포도막염과 이차성 녹내장을 유발한 비소세포 폐암의 홍채 전이 1예 - 문지연; 인정희; 조인환 (Daihan angwa haghoi jabji, 2024)
목적: 앞포도막염과 이차성 녹내장을 유발한 비소세포 폐암의 홍채 전이를 경험하였기에 이를 보고하고자 한다. 증례요약: 63세 여자 환자가 우안 안통과 시력저하를 주소로 내원하였다. 2년 전부터 비소세포 폐암 진단 하에 전신 화학요법과 방사선 치료를 받고 있었다. 최대 교정 시력 우안 0.63, 좌안 0.8이었고, 안압은 우안 52 mmHg였다. 전방 내 1+의 염증반응과 홍채 전반에 다발성 원형 결절들이 관찰되었다. 최대한의 안압하강제와 스테로이드제를 점안하고 탄산탈수효소억제제(acetazolamide)를 복용하였으며, 레이저 섬유주 성형술을 시행하였으나 안압은 조절되지 않았고 홍채 결절들도 변화가 없었다. 폐암의 홍채 전이 가능성이 있어 홍채 조직 생검 및 안방수 세포 검사를 시행하였다. 방수 내 악성 종양 세포는 음성이었으나 조직병리검사 결과 비소세포 폐암의 홍채 전이를 확인하였다. 폐암의 재병기를 시행하였고 폐의 좌상측엽, 골반뼈 전이가 새로 발견되었다. 결론: 조직병리검사를 통해 악성 종양의 홍채 전이를 확진할 수 있고, 안증상이 있는 폐암 환자에서 안과적 선별검사가 전이의 신속한 발견에 도움이 될 수 있다. Purpose: To report an iris metastasis of non-small-cell lung cancer inducing anterior uveitis and secondary glaucoma. Case summary: A 63-year-old woman presented to our hospital with vision impairment and pain in her right eye. She had been receiving systemic chemotherapy and radiation therapy to manage non-small-cell lung cancer for 2 years. Her best-corrected visual acuities were 25/40 oculus dexter (OD) and 20/25 oculus sinister; intraocular pressure was 52 mmHg OD. Slit-lamp examination revealed multiple round iris nodules and a 1+ inflammatory response in the anterior chamber of the right eye. Despite the maximimal tolerated medical therapy and laser trabeculotomy, the intraocular pressure was not controlled. Because iris metastasis of non-small-cell lung cancer was suspected, aqueous humor cytology and iris tissue biopsy were performed. Cytological analysis did not reveal malignant cells, but histopathological examination confirmed iris metastasis of non-small-cell lung cancer. A restaging procedure for lung cancer was performed, revealing new findings of lung and pelvic bone metastasis. Conclusions: Through histopathological examination, it is possible to confirm iris metastasis of malignant tumors. Ophthalmological screening tests in lung cancer patients with ocular symptoms can facilitate rapid detection of metastasis. KCI Citation Count: 0